Mutation Typing Using Electrophoresis and Gel-Immobilized AcryditeTM Probes. (September 1998) - Kenney, Mary; Ray, Satyajit; Boles, T. Christian
A new electrophoresis technology for hybridization-based sequence detection and mutation typing is described. Intrinsic to this approach is copolymerization of specially modified oligonucleotide probes directly into polyacrylamide gels. Electrophoresis of singlestranded samples through gels containing specific immobilized probes results in hybridization-mediated capture of complementary targets. By increasing gel temperature or including denaturants in the buffer, the method can be used to type single-nucleotide polymorphisms. The method can easily be adapted to type mutations in PCR-amplified samples. Acrydite TM gel technology will also be useful for many other applications, including hybridization-based diagnostics, analysis of gene expression and purification of nucleic acids from biological samples.